Evaluación de Trichoderma spp comercial y nativo en forma líquido y sólido para el incremento de la actividad microbiológica sobre un suelo erosionado en CEYPSA, Sector Salache, Cantón Latacunga, Provincia de Cotopaxi 2021. - Olivo Molina, Shirley Patricia (2021)
This research project was carried out in the Agronomy laboratories of the Technical University of Cotopaxi CEYPSA experimental center (Latitude 00 ° 59 ”47.68” North; Longitude 78 ° 37 ”19.16” West; Altitude 2750 masl), where commercial and native Trichoderma spp was evaluated in liquid and solid form to increase the microbiological activity on an eroded soil in CEYPSA, soil samples were collected and rice traps were made to capture microorganisms, for this we proceeded with a Hoe make a small hole to be able to insert the glass with the already prepared substrate, the traps were left there for approximately fifteen days for their subsequent removal. In addition, a completely randomized design (DCA) was proposed with a factorial arrangement of (2x2 + 1) with 3 repetitions, giving a total of 13 experimental units. The following were evaluated: population of fungi 10-3, fungi 10-4, bacteria 10-3, bacteria 10-4, and CO2. With these data, the statistical analysis of variance (ADEVA) was performed, and Tukey significance test at 5%, having the following results, 7 days after inoculation of Trichodermas in a population of fungi 10-3 with 881.33 CFU was for Solid native Trichoderma that was located in the “A” range, while the control with 361 CFU was located in the “D” range, thus being the worst treatment, within 14 days after the inoculation of Trichodermas in the fungal population. 10-3 with 956 CFU was for solid native Trichoderma that was in the “A” rank, while the control with 457 CFU was in the “D” rank. Regarding bacteria 7 days after the inoculation of Trichodermas in a population of bacteria 10-3 with 556.33 CFU, it was for solid native Trichoderma that was located in the “A” range, while the control with 294 CFU was located in the range "B", thus being the worst treatment, within 14 days after the inoculation of Trichodermas in a population of bacteria 10-3 with 626 CFU was for solid native Trichoderma that was located in the range "A", while the Witness with 300 CFU was in rank “B”. Finally, we have the result for CO2 7 days after Trichodermas inoculation, it did not present any statistical significance because the values were similar, within 14 days after Trichodermas inoculationthe following values were obtained with 5,87 mg / 100gr was for solid native Trichoderma that was located in the "A" range, while the control with 2.64 mg / 100gr that was located in the "C" range.